Italian Nurses' experiences during the COVID‐19 pandemic: a qualitative analysis of internet posts. (17th March 2021) - Fontanini, Roberta; Visintini, Erica; Rossettini, Giacomo; Caruzzo, Davide; Longhini, Jessica; Palese, Alvisa
Abstract : Aim: To investigate the experience of Italian nurses during the first wave of the COVID‐19 outbreak by analysing professional social media posts. Background: The COVID‐19 outbreak has overwhelmed health care institutions; as a consequence, nurses' lives and psycho‐physical health have been affected. Introduction: The COVID‐19 pandemic forced nurses to work in physically and psychologically stressful conditions impacting on their life. Methods: A qualitative descriptive study. All narratives (texts and videos) posted by nurses from the 23 rd of February 2020 to the 3 rd of May (from the start of the outbreak to the end of the first lockdown) were analysed and published on the five most popular Italian professional social media platforms. The Consolidated Criteria for Reporting Qualitative research guidelines were followed. Results: Five themes emerged from the 380 narratives explored: 'Sharing what is happening within myself'; 'Experiencing unprecedented working conditions'; 'Experiencing a deep change'; 'Failing to rehabilitate the image of nurses in society'; and 'Do not abandon us'. Even though nurses appreciated the recognition of their communities, they still felt devalued and not recognized as professionals. Discussion: Several psychological, physical, social and professional implications emerged from nurses working during the COVID‐19 pandemic. Despite being highly praised, nurses perceived they had failed in rehabilitating the image of nurses in society. Conclusion: The experience of working during the COVID‐19 pandemic represented a traumatic event for nurses but it offered them personal and professional growth opportunities. Implications for nursing practice, nursing policy and health policy: Supporting nurses' mental health is highly recommended, together with a cultural investment on nurses' role recognition, and a zero‐tolerance policy towards violence and aggression towards nurses.